Forced Convection Heat Transfer Coefficients - Bengtson, Harlan (McGraw-Hill's AccessEngineering., 2014)
The most time consuming part of any convection heat transfer calculation is obtaining a good value for the convection heat transfer coefficient. This Excel workbook calculates the convection coefficient for six forced convection heat transfer configurations: 1. Laminar pipe flow 2. Turbulent pipe flow 3. Turbulent flow through an annulus 4. Turbulent flow through a non-circular duct 5. Flow normal to a horizontal cylinder 6. Flow past a flat plate. You can select from any of 74 liquids and the workbook will calculate the liquid properties required.